Overview of Skin Whitening Agents: Drugs and Cosmetic Products - Céline Couteau; Laurence Coiffard (Cosmetics, 2016)
Depigmentation and skin lightening products, which have been in use for ages in Asian countries where skin whiteness is a major esthetic criterion, are now also highly valued by Western populations, who expose themselves excessively to the sun and develop skin spots as a consequence. After discussing the various possible mechanisms of depigmentation, the different molecules that can be used as well as the status of the products containing them will now be presented. Hydroquinone and derivatives thereof, retinoids, alpha- and beta-hydroxy acids, ascorbic acid, divalent ion chelators, kojic acid, azelaic acid, as well as diverse herbal extracts are described in terms of their efficacy and safety. Since a genuine effect (without toxic effects) is difficult to obtain, prevention by using sunscreen products is always preferable.